COMPARISON OF THE EFFECTIVENESS OF TWO LEVELS OF SUCTION PRESSURE ON OXYGEN SATURATION IN PATIENTS WITH ENDOTRACHEAL TUBE - Muhaji Muhaji; Bedjo Santoso; Putrono Putrono (Belitung Nursing Journal, 2017)
Background: Endotracheal suctioning is one of the common supportive measures in intensive care units (ICU), which may be related to complications such as hypoxia. However, a questionable efficacy is still identified to choose suctioning pressure between 130 mmHg and 140 mmHg that is effective for patients with endotracheal tube.Objective: To compare the effectiveness of 130 mmHg and 140 mmHg suctioning pressure on oxygen saturation in patients with endotracheal tube.Methods: This research used a quasi-experimental design with pretest and posttest group. The study was conducted from 31 January to 1 March 2017 in the Hospital of Panti Wilasa Citarum and Hospital of Roemani Muhammadiyah Semarang Indonesia. There were 30 samples recruited using consecutive sampling, with 15 assigned in the 130 mmHg and 140 mmHg suctioning pressure group. Pulse oximetry was used to measure oxygen saturation. Paired t-test and Independent t-test were used for data analysis.Results: Findings showed that there was a statistically significant effect of 130 and 140 mmHg suctioning pressure on oxygen saturation in patients with endotracheal tube with p-value <0.05. There was a significant mean difference of oxygen saturation between 130 mmHg and 140 mmHg suctioning pressure group with p-value 0.004 (<0.05). The mean difference of oxygen saturation between both groups was 13.157.Conclusion: The 140-mmHg suctioning pressure is more effective compared with 130 mmHg suctioning pressure in increasing oxygen saturation in patients with endotracheal tube.